2013
DOI: 10.1080/1357650x.2012.687002
|View full text |Cite
|
Sign up to set email alerts
|

Laterality of suckling behaviour in three zebra species

Abstract: Although side preference while suckling is an easily characterised lateralised behaviour, few studies have been conducted. We observed laterality in suckling behaviour in three captive zebra species to test two hypotheses: laterality affected by the foal (motor laterality) and laterality affected by the mother. In total we observed 35 foals of Grevy's, plains, and mountain zebra in two zoos and recorded 5128 successful suckling bouts and 9095 unsuccessful suckling attempts. At the population level the only fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…This greater milk production by the left teats seems consistent both at the individual and population level, and agree with the preferential suckling from the left side previously observed in monkeys, whales and equids [16][17][18][19][20][21], suggesting a possible connection. However, these side preferences cannot be directly linked to nipple preference since it can also be related to motor lateralization [20,21]. These axial differences in milk production and composition may be mediated by the effect of prolactin [33] and Fig.…”
Section: Axial Differences In Milk Productionsupporting
confidence: 90%
See 1 more Smart Citation
“…This greater milk production by the left teats seems consistent both at the individual and population level, and agree with the preferential suckling from the left side previously observed in monkeys, whales and equids [16][17][18][19][20][21], suggesting a possible connection. However, these side preferences cannot be directly linked to nipple preference since it can also be related to motor lateralization [20,21]. These axial differences in milk production and composition may be mediated by the effect of prolactin [33] and Fig.…”
Section: Axial Differences In Milk Productionsupporting
confidence: 90%
“…Thereafter it was found that sperm whales also favoured suckling from the left side [19]. The same case was seen in zebra foals [20] and horses [21] as well, but these left-side preferences have been explained as motor-related due to the fact that all nipples can be reached from both sides. Nevertheless, this repeated pattern is surprising, and deserves further study as it suggests the possibility of differential milk production being biased to a preferred side.…”
Section: Introductionmentioning
confidence: 78%